Comparative performance analyses of irreversible OMCE (Otto Miller cycle engine)-DiMCE (Diesel miller cycle engine)-DMCE (Dual Miller cycle engine) - Gonca, Guven (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
In this paper, comparative performance analyses of the irreversible OMCE (Otto Miller cycle engine), DiMCE (Diesel Miller cycle engine) and DMCE (Dual Miller cycle engine) based on the MP (maximum dimensionless power) output, MPD (maximum dimensionless power density) and MEF (maximum thermal efficiency) criteria have been performed by taking irreversibility due to irreversible-adiabatic compression and expansion processes into account. The maximum values of the thermal efficiency, dimensionless power output and dimensionless power density are obtained depending on pressure ratio, stroke ratio, cut-off ratio, miller cycle ratio, exhaust temperature ratio, cycle temperature ratio and cycle pressure ratio and the isentropic efficiencies of irreversible-adiabatic processes. The engine design parameters at the MP, MPD and MEF conditions are determined and their variations are investigated with respect to miller cycle ratio. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Miller cycle; Thermodynamic analysis; Performance optimization; Power output; Power density; Thermal efficiency; VARIABLE SPECIFIC-HEATS; MAXIMUM POWER-DENSITY; EXHAUST-GAS RECIRCULATION; INJECTED DIESEL-ENGINE; WORKING FLUID; OTTO-CYCLE; EMISSION PARAMETERS; COMBUSTION; FRICTION; OPTIMIZATION; Thermodynamics; Energy & Fuels